Reasonableness in the Concept of Reasonable Accommodation - de Asís Roig, Rafael (The Age of Human Rights Journal, 2016)
Reasonable accommodation is one of the pillars upon which the recognition of the rights of people with disabilities rests. It acquires its full meaning when understood in connection with the concept of universal design, since both concepts fall within the framework of universal accessibility. An accurate understanding of reasonable accommodation requires, on the one hand, clarifying its connection with universal design and accessibility, and on the other, unraveling what “reasonable” means. The reasonableness in accommodation takes to three kinds of reflections. On the one hand the one concerning non-discrimination, which requires to assess, when examining whether the adjustment is justified or not, if it entails a violation of the principle of equality (since it differentiates or it does not, in an unjustified manner, thus harming a human right such as accessibility). In this justifying test there is an essential methodological tool at hand, which shall be regarded as the second great reflection on reasonableness in accommodation: the principle of proportionality. In virtue of this principle, the reasonableness test requires facing the adjustment’s adequacy and necessity and, in addition to that, the advantages or sacrifices that produces on rights. And since both of these reflections do not ensure a single answer, reasonableness requires a last reflection on the basis of acceptability. The adjustment’s justification, or the lack of it, shall be subject to the community’s acceptance or rejection.